PENGARUH DISIPLIN, LINGKUNGAN ORGANISASI DAN LOYALITAS TERHADAP KINERJA PEGAWAI DINAS KESEHATAN KABUPATEN ACEH TAMIANG - Afrinalda . (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2020)
The formulation of this research is whether there is an influence of discipline, environment and loyalty work to the performance of officers in the health Department of Aceh Tamiang District, and the purpose of this research is to know and analyze the influence of discipline, Environmental organization and loyalty to the performance of officers in the Health office of Aceh Tamiang District. The method used in this research is the method of quantitative scriptive analysis using multiple linear regression with the measurement of Likert scale. The samples used in this study amounted to 33 employees. The results showed that simultaneously the variable discipline, organizational environment, loyalty has significant effect on performance with a significance value of 0.001 B. The discipline has a significant impact on the performance of officers at the Aceh Tamiang District health Office with significance value of 0.000. The organizational environment has a significant effect on the performance of employees at the Aceh Tamiang District Health Department with significance value of 0.000. Further, the work loyalty has a significant effect on the performance of officers in Aceh Tamiang District Health Department with significance value of 0.000 Simultaneously